Pengaruh Pemberian Triacontanol terhadap Produksi dan Viabilitas Benih Ketimun (Cucumis sativus L.) - Agatha Widhi B; Memen Surahman; Bambang S. Purwoko (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
The objective of this experiment was to determine the effect of triacontanol on cucumber production and viability. A comletely randomized design was used, consisting two factors i.e. concentration and time of application. Concentration consists of 5 levels: 0, 0.01, 0.1, 1.0, and 10.0 mg/l while time of application consists of 3 leveles: 2 weeks after planting (W AP), 4 W AP, and 2 & 4 W AP. Concentration, time of application and interaction of the two factors were not significant on vegetative and reproductive variables but were significant on seed weight index, and seed variability. Concentration of O.O1 mg/l and application of 4 WAP gave the best effect on seed viability. (p.11)   Key words: Triacontanol, Seed, Cucumber